INTEGRATING HUMAN CAPITAL INFORMATION SYSTEMS AND EMPLOYEE SELF-SERVICE IN VIRTUAL OFFICES FOR ENHANCED EMPLOYEE PERFORMANCE - Neneng Hayati; Erwin Yulianto (Faculty of Economic and Business, University of Pasundan, 2026)
This study examines the integration of Human Capital Information Systems (HCIS) and Employee Self-Service (ESS) in a virtual office environment to enhance employee performance. Using a qualitative exploratory case study, data were collected through interviews with 12 participants, system observations, and document analysis, and interpreted using the Technology Acceptance Model (TAM) and Human Capital Theory. Findings show that HCIS–ESS integration improves administrative efficiency, work flexibility, and HR service quality. Employees perceived the system as useful and easy to use, supporting continued adoption. Key challenges included unstable internet connectivity, limited system customization, and varying digital literacy. Successful implementation required organizational readiness, leadership commitment, clear standard operating procedures, and continuous technical support. This study contributes qualitative evidence on digital HRM transformation through HCIS–ESS integration in virtual work environments.